Morphological and morphometric characteristics of the epididymis in the Neotropical bats Eumops glaucinus and Molossus molossus (Chiroptera: Molossidae). - Beguelini, Mateus R.; Sergio, Bruno F.S.; Leme, Fabio L.J.; Taboga, Sebastiao R.; Morielle-Versute, Eliana (My University, 2010)
The ability of certain species of bats to store viable spermatozoa in the cauda epididymis, for periods of many months beyond the end of spermatogenesis was first recognized over a century ago. However, information about the bat epididymis is still scarce or absent. Thus, this study aimed to characterize and to compare morphologically and morphometrically the regional histology of the epididymis of Eumops glaucinus and Molossus molossus (Chiroptera: Molossidae). Histologically, the epididymis of both species was subdivided into 4 segments: initial segment, caput, corpus and cauda. In comparing the two species, it was observed that the tubular and luminal diameters and percentage of interstitial tissue showed significant differences in all segments. The epithelial height, in both, is greater in the initial segment with a decrease until the cauda epididymis. In relation to the luminal diameter, both species showed a gradual increase from the initial segment to the cauda. The percentage of epithelium, lumen and interstitial tissue varied between both, sometimes M. molossus showing a significantly higher percentage, and other times, E. glaucinus. In both species, the principal cell was the most abundant (> 77%), followed by basal cells at approximately 13% and apical cells at 4% in all segments. Spermatozoa were observed in greater amounts in corpus and cauda epididymis segments. In summary, ours results show that, despite that the species analyzed belong to different genera and have different breeding cycles, the epididymis exhibits similarities in the two species and morphometric and composition differences compared to the majority of mammals.